Diseño de una Guía de Medicina Tradicional en la Parroquia Angamarca, Cantón Pujilí, Provincia de Cotopaxi - Mejía Riera, Jessica Lucía (2019)
The lack of knowledge and interest on the part of the authorities and of the new population generations; within the subject in traditional medicine, all the practices, rites and elements used in it, only remain in memory of those who practice said medicine, the INPC, through its technical data sheets, facilitates these studies, capturing in a document all the cultural memories that exist within Ecuador, today has seen the growth of interest by educational institutions and their students which may set a precedent for the future of culture in the country, a sample of that is the present work that was carried out in the province of Cotopaxi, Pujili canton, Angamarca